ANALISIS PENCAPAIAN DIMENSI PENGETAHUAN PADA MATERI GERAK PARABOLA DITINJAU DARI GAYA BELAJAR DI SMAN 2 TEMPUNAK - Pinansius Lenggo; Tomo Djudin; Erwina Oktavianty (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractNational curriculum explains that students should be able mastering knowledge of factual, conceptual, procedural, and metacognitive after studying materials, particularly science education materials. That after studying teaching material, students were required to be able to master. However, some students in Indonesia, especially the Department of Science (Natural Sciences) are still having difficulties in factual,conceptual and procedural knowledge. One internal factor that affects the difficulties of students is learning style. The main objective of this study was to analyze the presence or absence of the effect of the achievement of the dimensions of knowledge on the material of the satellite dish influenced by the learning style of students in SMAN 2 Tempunak. To find out the learning style of students used the learning style questionnaire according to Deporter and Hernacki. To measure the achievement of the dimensions of students’ knowledge used multiple choice tests with each dimension of seven questions. This study uses descriptive methods with correlational forms. The sample in this study numbered thirty students of class X MIPA. The result of the data analysis using Chi squared (χ2 = 2.911) the findings showed insignificant. The results showed that learning styles did not affect the analysis of the dimensions of students’ knowledge.Keywords: Descriptive, Knowledge Dimensions, Learning Style